First navicular remains of a European adapiform (Anchomomys frontanyensis) from the Middle Eocene of the Eastern Pyrenees (Catalonia, Spain): implications for early primate locomotor behavior and navicular evolution. Issue 139 (February 2020) - Marigó, Judit; Minwer-Barakat, Raef; Moyà-Solà, Salvador; Boyer, Doug M.
Abstract: We describe the first known navicular bones for an Eocene euprimate from Europe and assess their implications for early patterns of locomotor evolution in primates. Recovered from the fossil site of Sant Jaume de Frontanyà-3C (Barcelona, Spain), the naviculars are attributed to Anchomomys frontanyensis . The small size of A. frontanyensis allows us to consider behavioral implications of comparisons with omomyiforms, regardless of allometric sources of navicular variation. Researchers usually consider omomyiforms to be more prone to leaping than contemporaneous adapiforms partly because of the more pronounced elongation of omomyiform tarsal elements. However, A. frontanyensis differs from other adapiforms and is similar to some omomyiforms in its more elongated navicular proportions. Although this might raise questions about attribution of these naviculars to A. frontanyensis, the elements exhibit clear strepsirrhine affinities leaving little doubt about the attribution: the bones' mesocuneiform facets contact their cuboid facets. We further propose that this strepsirrhine-specific feature in A. frontanyensis and other adapiforms reflects use of more inverted foot postures and potentially smaller substrates than sympatric omomyiforms that lack it. Thus substrate differences may have influenced niche partitioning in Eocene euprimate communities along with differences in locomotor agility. As previous studies on the astragalus and the calcaneus have suggested, this study on the navicular is consistent with the hypothesis that the locomotor mode of A. frontanyensis was similar to that of extant cheirogaleids, especially species of Microcebus and Mirza .